The Fps/Fes protein-tyrosine kinase promotes angiogenesis in transgenic mice. - Greer, P (1994)
The fps/fes proto-oncogene encodes a cytoplasmic protein-tyrosine kinase known to be highly expressed in hematopoietic cells. To investigate fps/fes biological function, an activating mutation was introduced into the human fps/fes gene which directs amino-terminal myristylation of the Fps/Fes protein. This mutant, myristylated protein induced transformation of Rat-2 fibroblasts. The mutant fps/fes allele was incorporated into the mouse germ line and was found to be appropriately expressed in transgenic mice, in a tissue-specific pattern indistinguishable from that of the endogenous mouse gene. These mice displayed widespread hypervascularity, progressing to multifocal hemangiomas. High levels of both the transgenic human and endogenous murine fps/fes transcripts were detected in vascular tumors by using RNase protection, and fps/fes transcripts were localized to endothelial cells of both the vascular tumors and normal blood vessels by in situ RNA hybridization. Primary human umbilical vein endothelial cultures were also shown to express fps/fes transcripts and the Fps/Fes tyrosine kinase. These results indicate that fps/fes expression is intrinsic to cells of the vascular endothelial lineage and suggest a direct role of the Fps/Fes protein-tyrosine kinase in the regulation of angiogenesis.